Enhanced Distributed Energy Efficient Clustering Protocol:Using Priority Queue - Kour, Updeep; Sharma, Sandeep (International Journal of Computer Sciences and Engineering, 2019)
Today WSN are highly approached technology that used to interact several sensor nodes corresponding to at least common application. The WSN is affected by the problem of energy dissipation of the sensor node that collects and report the specific data to application monitoring node. The main reason to develop WSN network is to maximize the lifetime of the batteries that are constrained by the nodes during transmission. The clustering mechanism is the best and most efficient one to resolve the issue with the requirement of energy in WSN. In clustering the network is divided into smaller clusters and each cluster includes one cluster head and members. It is very much useful for reducing the energy dissipation and enhancing the lifetime of the network. In this paper we propose new clustering protocol Enhanced DEEC(Distributed Energy Efficient Clustering ) along with priority queue to balance the energy in the WSN network and prolonging the lifetime of the network. The simulation results revealed the performace of the proposed technique is better than existing protocol DEEC. Energy consumed during overall packet transmission, packet drop ratio, number of packets transmitted to the base station and cluster head are considered parameters.